Gastrodia albidoides (Orchidaceae: Epidendroideae), a new species from Yunnan, China - Tan, Yun-Hong; Hsu, Tian-Chuan; Pan, Bo; Li, Jian-Wu; Liu, Qiang (Phytotaxa, 2012)
A new species, Gastrodia albidoides (Orchidaceae: Epidendroideae, Gastrodieae) from Yunnan, China, is described and illustrated. It is closely related to G. theana and G. albida but can be distinguished by an almost smooth perianth tube, lateral sepals fused to ½ their length, whitish and unthickened petals, a well-developed rostellum and distinct column foot.